Critical Systems Heuristics - Evaluation, Better
Critical System Heuristics (CSH) provides a framework of questions abo ut a program including what is (and what ought to be) its purpose and its source of legitimacy and who are (and who ought to be) its intende d beneficiaries. CSH, as developed by Werner Ulrich and later elaborat ed upon in collaboration with Martin Reynolds, is an approach used to surface, elaborate, and critically consider boundary judgments, that i s, the ways in which people/groups decide what is relevant to the syst em of interest (any situation of concern). CSH is concerned not only w ith purposive evaluation, where the system or project has a predefined goal and the focus lies in evaluating the means of reaching it, but a lso more broadly with purposeful evaluation, where both the means and the ends become subjects of inquiry. CSH rests on the foundations of s ystems thinking and practical philosophy, both of which emphasize the 'infinite richness' of the real world. In this view, understandings of any situation are inherently incomplete, and therefore based on the s elective application of knowledge. By systematically questioning the s ources of motivation, control, expertise, and legitimation in the syst em of interest, CSH allows users to make their boundary judgments expl icit and defensible. The immediate goal of a CSH evaluation is to elab orate multiple perspectives on a given situation, but the broader aim is to share these perspectives and thereby cut down on actors 'talking past' each other by promoting mutual understanding.